1974
DOI: 10.1001/archneur.1974.00490370044005
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Forms of Motor Neuron Disease

Abstract: A 50-year-old battery worker had clinical signs of motor neuron disease: weakness, wasting, and active reflexes. Nerve conduction velocities, electromyogram, and motor unit territory indicated that the disorder was neuronal. Biochemical abnormalities were characteristic of lead in-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

1977
1977
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 23 publications
0
17
0
2
Order By: Relevance
“…Case reports have documented occurrence of an ALS-like syndrome following lead poisoning [20][21][22][23][24] . Many of these cases showed some improvement following chelation therapy, which lowers blood lead levels, suggesting that they did not have ALS but rather a neurotoxic response to continuing lead exposure.…”
mentioning
confidence: 99%
“…Case reports have documented occurrence of an ALS-like syndrome following lead poisoning [20][21][22][23][24] . Many of these cases showed some improvement following chelation therapy, which lowers blood lead levels, suggesting that they did not have ALS but rather a neurotoxic response to continuing lead exposure.…”
mentioning
confidence: 99%
“…Although her neurological presentation was not typical of lead neurotoxicity, 4 there have been case reports of lead poisoning mimicking MND. 5,6 Moreover, an animal study showed that anterior horn cells were sensitive to lead toxicity. 7 Chelation therapy with succimer (dimercaptosuccinic acid [DMSA]) was started in view of these possibilities.…”
Section: Chinese Talismans As a Source Of Lead Exposure Case Reportmentioning
confidence: 99%
“…4 Severe form of lead-induced peripheral neuropathy has been reported in causing generalised weakness mimicking MND. 5,6 Unlike MND, leadinduced peripheral neuropathy is associated with increased body burden of lead, a temporal sequence between lead exposure and progression of muscle weakness, clinical stabilisation or remission after removal from exposure, and systemic involvement with other features of lead poisoning such as anaemia and gastro-intestinal disturbance. 17 Chelation therapy is usually not indicated in asymptomatic adults with BLL of <3.36 µmol/L (70 µg/dL).…”
Section: -11mentioning
confidence: 99%
“…Existen otros exámenes de laboratorio de menor especificidad, pero que pueden coadyuvar al diagnóstico, como tiempo de vida del hematíe, velocidad de conducción en nervios periféricos, sobre todo en los del grupo muscular que más usa el trabajador, pruebas neuro-comportacionales, pruebas de función renal, etc. ( [33][34][35][36] ).…”
Section: Diagnósticounclassified